Three‐to‐Six‐Day Air–Sea Oscillation in Models and Observations. Issue 10 (17th May 2020) - Strobach, Ehud; Molod, Andrea; Trayanov, Atanas; Forget, Gael; Campin, Jean‐Michel; Hill, Chris; Menemenlis, Dimitris
Abstract: Analysis of coupled ocean‐atmosphere numerical simulations revealed a widespread oscillation of sea surface temperature (SST) and surface wind anomalies with a cyclic nature characterized by a period of 3 to 6 days. Similar oscillations were also found in buoy data at different locations around the globe and in an atmospheric reanalysis, albeit the oscillations were noisier and stronger in the observations, and they were weaker and longer period in the atmospheric reanalysis. These oscillations did not, however, develop in an atmosphere‐only simulation, suggesting the importance of ocean–atmosphere coupling for simulating this phenomenon. We propose a mechanism for this interaction involving a feedback between SST and surface wind. Key Points: Goddard Earth Observing System‐Massachusetts Institute of Technology general circulation mode is able to reproduce past observed sea surface temperature (SST) and wind stress correlations Analysis of higher temporal resolution SST and wind speed reveals several days SST wind speed cycle We suggest a mechanism for the cycle